Experimental Study of Slurry Flow in Mining-Induced Fractures during Longwall Overburden Grout Injection - Dayang Xuan; Jian Li; Kaidan Zheng; Jialin Xu (Geofluids)
Slurry flow in mining-induced overburden fractures is an important theoretical concept for the grouting design of longwall overburden grout injection engineering. In this study, a visual experimental simulation system of longwall overburden grouting was designed to study the flow, pressure distribution, consolidation, and fill thickness of fly ash slurry in overburden bedding separation. Experiments showed that the slurry generates a radial and bidirectional flow during nonpressure grouting and presents itself as an approximately elliptical dominant flow channel under pressure injection. This channel expanded horizontally along the strike direction and gradually became tabular. The slurry pressure increased as the grouting time increased. Although the pressure curves at different locations exhibited similar trends, their values did not decrease as the distance from the borehole center decreased during observations. Bleeding and consolidation occurred in the slurry as soon as it flowed out of the borehole to the fracture, and the degree of consolidation increased as a function of the distance from the injection borehole. The bleeding water gathered continually to the boundary of the bedding separation fracture and was then seeped to and stored by the underlying strata based on the injection pressure. The final injection fill is manifested as a half pace with a large thickness at the center. This research provides a theoretical basis for the design and optimization of overburden grout injection in underground longwall mining.